2021
DOI: 10.3390/ijms22094858
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Plasticity in Signaling Pathways Involved in Motor Recovery after Spinal Cord Injury

Abstract: Spinal cord injury (SCI) leads to numerous chronic and debilitating functional deficits that greatly affect quality of life. While many pharmacological interventions have been explored, the current unsurpassed therapy for most SCI sequalae is exercise. Exercise has an expansive influence on peripheral health and function, and by activating the relevant neural pathways, exercise also ameliorates numerous disorders of the central nervous system (CNS). While the exact mechanisms by which this occurs are still bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 180 publications
(293 reference statements)
0
36
0
Order By: Relevance
“…Both clinical and animal studies have found [ 10 , 17 20 ] that activity-based functional training can improve spasticity after SCI, and this effect may be associated with the increased synthesis of the tropomyosin-related kinase B (TrkB), brain-derived neurotrophic factor (BDNF), GABA, and KCC2 in the spinal cord. Overexpression of BDNF in the damaged spinal cord increases the expression of glutamic acid decarboxylase 65/67 (GAD-65/67, the key enzymes in GABA synthesis), enhances inhibitory effects within the spinal cord, and promotes functional recovery in SCI rats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical and animal studies have found [ 10 , 17 20 ] that activity-based functional training can improve spasticity after SCI, and this effect may be associated with the increased synthesis of the tropomyosin-related kinase B (TrkB), brain-derived neurotrophic factor (BDNF), GABA, and KCC2 in the spinal cord. Overexpression of BDNF in the damaged spinal cord increases the expression of glutamic acid decarboxylase 65/67 (GAD-65/67, the key enzymes in GABA synthesis), enhances inhibitory effects within the spinal cord, and promotes functional recovery in SCI rats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic AMP response element-binding protein (CREB) and its phosphorylated counterpart (p-CREB) may involve in increasing GAD-65/67 expressions through regulating gene transcription downstream of TrkB signaling [ 10 ]. However, further investigations are required to determine whether exercise training can modulate the expression of GAD-65/67 and KCC2 in the distal of the spinal cord, enhance spinal inhibition, and improve spasticity via TrkB signaling after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroplasticity refers to the capacity of the nervous system to modify itself in response to experience and injury [ 18 ]. Therefore, BDNF facilitates exercise-based recovery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no FDA-approved treatment that can prevent the development of secondary SCI, nor one that induces regenerative processes [ 5 ]. Nonetheless, a moderate degree of functional recovery can be achieved using rehabilitative motor training [ 38 , 55 , 56 ]. Rehabilitation is probably one of the most important interventions following neurotrauma, and it can potentially improve a patient’s quality of life significantly.…”
Section: Discussionmentioning
confidence: 99%